P384 Postoperative Endoscopic Recurrence In Patients With Crohn's Disease After "Curative" Ileocecal Resection on Prophylaxis Treatment With Either Anti-TNFs, Vedolizumab or Ustekinumab: A Real-World Multicentre European Study. (21st January 2022) - Yanai, H; Amir Barak, H; Kagramanova, A; Knyazev, O; Sabino, J; Haenen, S; Mantzaris, G J; Mountaki, K; Pugliese, D; Armuzzi, A; Furfaro, F; Fiorino, G; et al.
Abstract: Background: Endoscopic post-operative recurrence (ePOR) is common following ileocecal resection (ICR) in patients with Crohn's disease (CD), reaching up to, 70% at, 1-year. In clinical trials, prophylaxis with anti-TNF therapies demonstrated a decrease in ePOR to around, 20% at, 1-year. Here we aimed to compare the effectiveness of vedolizumab (VDZ) and ustekinumab (UST) to anti-TNFs for preventing ePOR after curative ICR in adults with CD in a real-world setting. Methods: This was a retrospective multicenter study, assessing patients with CD >17years who underwent ICR between, 2015–2019, started prophylaxis within six months of surgery, and underwent an ileocolonoscopy ≥ four months after prophylaxis. ePOR (Rutgeerts score ≥ i2 or colonic-segmental-SES-CD≥6) was assessed at, 12, 24, 36-months periods post-surgery. Multivariate logistic regression was used to assess risk factors for ePOR, and IPTW was performed to compare the effectiveness between agents. Results: Included, 297 patients [53.9% males, age-at-diagnosis, 24(19–32) years (median;IQR), age-at-ICR, 34(26–43)years (median;IQR), 18.5% current-smokers]. Of these, 17.2% had previous-ICR, 8.1% were biologic naïve, 65.7% anti-TNF experienced, and, 28.6% exposed to, 2 biologics. Overall, 224, 39 and, 34 patients received respectively anti-TNFs, VDZ or UST for prevention of POR. Patients on VDZ and UST were more likely to be biologic experienced or post previous-ICR. ePOR rates for the entire cohort, anti-TNF, VDZ and UST were:, 41.8%, 40.2%, 33%, and, 61.8% at, 12-months, 49.0%, 46.5%, 44.4%, and, 72.4% at, 24- months, and, 48.6%, 47.9%, 44.0% and, 62.5% at, 36-months, respectively. Risk factors for ePOR: past infliximab (Adj.OR =1.73 [95% CI:, 1.01–2.97], p=0.045) or adalimumab (Adj.OR = 2.32 [95% CI:, 1.35–4.01], p=0.002), and technical aspects of anastomosis. After controlling for the disparities between groups by the IPTW method risk of ePOR at, 12-months was comparable between patients on anti-TNFs vs VDZ or anti-TNFs vs UST. However, comparison between VDZ vs UST groups revealed that patients on UST were at a higher risk for ePOR at, 12-months (OR=3.75 [95% CI:, 1.33–10.6]), p=0.012. Conclusion: Prevention of ePOR was successful in ~60% of patients at, 12-months period. Patients on prophylaxis VDZ or UST consisted of a distinct, more refractory group with higher rates of ePOR. Post-operative treatment with UST or VDZ resulted in a similar risk of ePOR when compared to post-operative prophylaxis with anti-TNF after controlling for disease severity.